The Role of 3D Printing in Advancing Automated Manufacturing Systems: Opportunities and Challenges - Antreas Kantaros; Christos Drosos; Michail Papoutsidakis; Evangelos Pallis; Theodore Ganetsos (Automation, 2025)
The integration of 3D printing technologies in automated manufacturing systems marks a significant progression in the manufacturing industry, enabling elevated degrees of customization, efficiency, and sustainability. This paper explores the synergy between 3D printing and automation by conducting a critical literature review combined with case study analysis, focusing on their roles in enhancing production lines within the framework of Industry 4.0 and smart factories. Key opportunities presented by this integration include mass customization at scale, reduced material waste, and improved just-in-time manufacturing processes. However, challenges related to quality control, scalability, and workforce adaptation remain critical issues that require careful consideration. The study also examines the emerging role of hybrid manufacturing systems that combine additive and subtractive processes, alongside the growing need for standardized regulations and frameworks to ensure consistency and safety. Case studies are highlighted, showcasing real-world applications of automated 3D printing technologies and AI-driven print optimization techniques. In conclusion, this paper contributes to advancing the scholarly understanding of automated 3D printing by synthesizing technical, organizational, and regulatory insights and outlining future trajectories for sustainable and agile production ecosystems.